2002
DOI: 10.1111/j.1748-5827.2002.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of aminoglutethimide in the treatment of pituitary‐dependent hyperadrenocorticism in the dog

Abstract: The aim of this study was to evaluate the efficacy and safety of aminoglutethimide in the treatment of dogs with pituitary-dependent hyperadrenocorticism (PDH). Ten dogs were diagnosed with PDH based on clinical and laboratory data, adrenal function tests (adrenocorticotropic hormone [ACTH] stimulation test and urinary cortisol/creatinine ratio [UCCR] combined with a high dose oral dexamethasone suppression test) and ultrasonographic evaluation of the adrenal glands. Aminoglutethimide was administered daily at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…On the other hand, some cases in past studies indicated that remission of myotonia symptoms, especially those of the temporalis muscle, tends to be difficult. In a few past case reports, myotonia of the limbs did not improve despite trilostane treatment [ 9 , 13 , 15 , 19 ]; in this case, as well as in previous cases, no sufficient therapeutic effects were observed on myotonia. The reason for different treatment responses between trismus and myotonia of the extremities is not clear.…”
supporting
confidence: 48%
See 2 more Smart Citations
“…On the other hand, some cases in past studies indicated that remission of myotonia symptoms, especially those of the temporalis muscle, tends to be difficult. In a few past case reports, myotonia of the limbs did not improve despite trilostane treatment [ 9 , 13 , 15 , 19 ]; in this case, as well as in previous cases, no sufficient therapeutic effects were observed on myotonia. The reason for different treatment responses between trismus and myotonia of the extremities is not clear.…”
supporting
confidence: 48%
“…In the young dogs, myotonia can occur as a hereditary condition in Chow Chow, Miniature Schnauzer, Labrador Retriever, Australian Cattle Dog, American Bulldog, and other breeds [ 1 , 5 , 6 , 16 , 17 ]. In an adult dog, acquired myotonia can also develop as an uncommon complication of hyperadrenocorticism [ 13 , 15 , 19 ]. The major clinical presentation of hyperadrenocorticism-associated myotonia is an abnormal gait due to stiff limbs [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In addition, there have been reports of the treatment of HAC using ketoconazole, selegiline hydrochloride, and aminoglutethimide. [6][7][8] Mitotane binds covalently to adrenal proteins before being converted to a reactive metabolite, resulting in the destruction of adrenal tissue. Destruction of the adrenal cortices can be partial or complete, depending on dose and frequency of administration.…”
mentioning
confidence: 99%
“…63 Selegiline (L-Deprenyl; Anipryl) is a monoamine oxidase-B inhibitor approved for the treatment of PDH, but it is not effective by itself. 64 Trilostane (not currently available in the United States) is a safe and effective inhibitor of steroidogenesis.…”
Section: Normal Pdh Atdhmentioning
confidence: 99%